Photoperiodic Response of Pinus patula Schiede and Deppe Seedlings - Ghosh, R. C.; Bhatnagar, H. P.; Uniyal, D. P. (Indian Forester, 1977)
Pot culture studies were conducted with the seedlings Pinus patula to determine the effect of different photoperiodic treatments on height growth, dry matter production and tracheid characteristics. The three treatments (Long day Short day and Normal day) used in this study have significant effect on all the characters studied. Long day treatment of 18 hours continuous light period has significantly improved height growth and dry matter of both roots and shoots of the seedlings. Pronounced differences in tracheid characters such as tracheid length, width, lumen diameter and cell wall thickness have been observed under different photoperiodic treatments.